Dental Patients' Involvement In Infection Control: Educational Aspects - Lucia Barlean; Ioan Danila; Dana Baciu (Romanian Society of Oral Rehabilitation, 2010)
The dental patients' education regarding the involvement in their own health care, based on the evaluation of their attitudes and knowledge in infection control represents a strategy to strengthen the safety of the dental treatment. The aim of this survey was to evaluate the knowledge and attitudes of dental patients towards cross-infection control measures in dental practices; Materials and methods. To assess the patients' approach a questionnaire-based survey was initiated, a total of 110 patients aged between 16 and 68 years being interviewed. Data was processed using SPSS 15.0 in terms of age, gender and level of education. Results: 83.6% of the patients trust the medical staff taking into account that it protects them against illness spread. 45.5% of the subjects looking forward to the implementation of infection control procedures. 89,0% of them require that the dentists wear gloves throughout the dental treatment whilst 63.6% prefer the protection mask . Conclusions Dental patients' awareness in terms of infection control must influence the dentists' choice of using the equipments and protocols in order to adopt the European safety standards during the dental treatment.